+0

# Factor z^2 − z − 3 = 0

0
220
2
+96

Factor z^2 − z − 3 = 0

Aug 27, 2018

#1
+391
+3

This quadratic, $$z^2 - z - 3 = 0$$ is a bit trickier. For this one, we need to use the quadratic formula, which is $$\frac{-b ± \sqrt{b^2 - 4ac}}{2a}$$.

When we plug in the values of $$a, b,$$ and $$c$$, we get $$\frac{-(-1) ± \sqrt{(-1)^2 - 4(1)(-3)}}{2(1)} = \frac{1±\sqrt{13}}{2}$$. This means $$z = \frac{1}{2} + \frac{1}{2}\sqrt{13}$$ or $$z = \frac{1}{2} + \frac{-1}{2}\sqrt{13}$$.

- Daisy

Aug 27, 2018

#1
+391
+3

This quadratic, $$z^2 - z - 3 = 0$$ is a bit trickier. For this one, we need to use the quadratic formula, which is $$\frac{-b ± \sqrt{b^2 - 4ac}}{2a}$$.

When we plug in the values of $$a, b,$$ and $$c$$, we get $$\frac{-(-1) ± \sqrt{(-1)^2 - 4(1)(-3)}}{2(1)} = \frac{1±\sqrt{13}}{2}$$. This means $$z = \frac{1}{2} + \frac{1}{2}\sqrt{13}$$ or $$z = \frac{1}{2} + \frac{-1}{2}\sqrt{13}$$.

- Daisy

dierdurst Aug 27, 2018
#2
+100569
+2

This is an irreducible quadratic  [ cannot be factored  ]

Aug 27, 2018